CONSUMER'S SATISFACTION OF MEDICAL LABORATORY SERVICES IN OUTPATIENT CARE IN MUNICIPALITY VARNA. - Emilia P. Georgieva; Galina R. Petrova; Todorka I. Kostadinova (Peytchinski Publishing, 2015)
The purpose of the medical laboratory service is to satisfy the needs of the patient and the community, which determines the social aspect of healthcare. Achieving real quality in the health system aims to provide and maintain a good level of health, functional capacity and patient satisfaction. Medical diagnostic tests have a key role in monitoring the pathological process, which is a set of measures and activities for prevention of the emergence, development and spread of diseases in people.